Comparing Cognitive Load Levels Among Family Members of the Critically Ill Exposed to Electronic Decision Aids - Pignatiello, Grant A. (Appl Nurs Res, 2019)
Cognitive load predicts one’s ability to process information and learn from decision support interventions. The present study compared intrinsic and extraneous cognitive load levels resulting from exposure to two different electronic decision aids. A convenience sample of ninety-seven surrogate decision makers for critically ill patients were randomly assigned to receive either a single dose of a video-based or avatar-based decision aid. Intrinsic and extraneous cognitive load levels among recipients of the video-based decision support resource were lower than recipients of the avatar-based decision support resource. After controlling for age, the observed differences in intrinsic cognitive load were not significantly different, whereas the observed differences in extraneous cognitive load remained. Extraneous cognitive load is a modifiable factor to consider for future developers of decision support interventions that may determine the efficacy of efforts to support patients and family members with decision making.